2014
DOI: 10.1126/scisignal.2005522
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of the long pentraxin PTX3 against histone-mediated endothelial cell cytotoxicity in sepsis

Abstract: Pentraxin 3 (PTX3), a member of the long pentraxin subfamily within the family of pentraxins, is a soluble pattern recognition molecule that functions in the innate immune system. Innate immunity affords the infected host protection against sepsis, a potentially life-threatening inflammatory response to infection. Extracellular histones are considered to be the main cause of septic death because of their cytotoxic effect on endothelial cells, which makes them a potential therapeutic target. We found that PTX3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 50 publications
0
36
0
Order By: Relevance
“…Not surprisingly, many plasma proteins that neutralize histones are highly negatively charged, such as heparin, 44 pentraxin-3, 45 C-reactive protein, 46 and inter-a inhibitor protein. 21 DNA may also efficiently neutralize the histone charge, and indeed, analogous to nucleosomes, we showed that both ssDNA and dsDNA neutralized the cytotoxicity induced by histones.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, many plasma proteins that neutralize histones are highly negatively charged, such as heparin, 44 pentraxin-3, 45 C-reactive protein, 46 and inter-a inhibitor protein. 21 DNA may also efficiently neutralize the histone charge, and indeed, analogous to nucleosomes, we showed that both ssDNA and dsDNA neutralized the cytotoxicity induced by histones.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several clinical investigations have demonstrated that elevated plasma Ptx3 levels are associated with cardiovascular [8,9] and chronic kidney diseases (CKD) [10,11]. Kenji Daigo et al demonstrated that the intraperitoneal administration of Ptx3 reduced mortality in mouse models of sepsis [12]. Furthermore, plasma Ptx3 levels are inversely associated with body mass index (BMI) suggesting that Ptx3 may play a role in obesity and metabolic syndrome [13,14].…”
Section: Introductionmentioning
confidence: 98%
“…These motifs confer on PTX3 N-terminal domain a propensity for forming a coiled-coil structure. The signal of the α-helix was detected by circular dichroic (CD) spectroscopy (8). Inforzato et al attributed the multimer formation of PTX3 to the inter- and intra-molecular disulfide bonds in the organization of the matrix (25) and proposed an asymmetric octamer structure for PTX3 based on biophysical analysis (26).…”
Section: Pentraxin 3: General Description and Role In Netsmentioning
confidence: 99%
“…In the effort to understand the molecular mechanisms of PTX3–histone complex formation, both direct and high-affinity binding between PTX3 and histones has been reported. Of note, it was found that the binding induced coaggregation of PTX3 with histones due to a disorder of the PTX3 secondary structure (Figures 2A,B) (8). A cell-based assay revealed that PTX3 blocks histone-mediated cytotoxic activity toward endothelial cells.…”
Section: Protective Role Of Ptx3 Against Extracellular Histones: Implmentioning
confidence: 99%
See 1 more Smart Citation